2016
DOI: 10.1002/smll.201601758
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized g‐C 3 N 4 Nanospheres as Catalytically Photoactive Linkers in MOF/g‐C 3 N 4 Composite of Hierarchical Pore Structure

Abstract: A unique composite of the copper-based metal-organic framework (Cu-benzene tricarboxylic acid (BTC)) with oxidized graphitic carbon nitride nanospheres is synthesized. For comparison, a hybrid material consisting of g-C N and Cu-BTC is also obtained. Their surface features are analyzed using Fourier transform infrared spectroscopy, X-ray diffraction, sorption of nitrogen, thermal analysis, scanning electron microscopy, photoluminescence, and diffuse reflectance UV-Vis spectroscopy. The results suggest that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(42 citation statements)
references
References 57 publications
(115 reference statements)
1
41
0
Order By: Relevance
“…[4] At present, various strategies have been developed to promote the photoactivity of pristine g-C 3 N 4 . [5] In addition to the exfoliation of g-C 3 N 4 , [6] g-C 3 N 4 with special geometrical shapes could profit from shorter diffusion pathways and higher specific surface area, [7] elevating the photocatalytic activity from that obtained with conventional bulk counterparts.T hus,agreat deal of effort has been devoted to endowing g-C 3 N 4 with specific nanostructures,such as g-C 3 N 4 nanosheets, [8] hollow nanospheres, [7] and porous frameworks. [9] Recent experimental and theoretical studies have shown the superior photocatalytic activity of g-C 3 N 4 nanotubes under visible light.…”
mentioning
confidence: 99%
“…[4] At present, various strategies have been developed to promote the photoactivity of pristine g-C 3 N 4 . [5] In addition to the exfoliation of g-C 3 N 4 , [6] g-C 3 N 4 with special geometrical shapes could profit from shorter diffusion pathways and higher specific surface area, [7] elevating the photocatalytic activity from that obtained with conventional bulk counterparts.T hus,agreat deal of effort has been devoted to endowing g-C 3 N 4 with specific nanostructures,such as g-C 3 N 4 nanosheets, [8] hollow nanospheres, [7] and porous frameworks. [9] Recent experimental and theoretical studies have shown the superior photocatalytic activity of g-C 3 N 4 nanotubes under visible light.…”
mentioning
confidence: 99%
“…For the synthesis process leading to true composites and not to physical mixtures, the interactions of a MOF phase and modifier functional groups are important. Thus, owing to these interactions, the composites of Cu-BTC and oxidized g-C 3 N 4 had hierarchical porosity and exhibited photoactive properties [23].Even though structural or chemical defects were not the focus of the synthesis procedure at the time of the introduction of MOF/other phase composites, the published results showed some distortion in the crystal structure, along with an increase in the porosity and in the population of metal centers [40,48]. Therefore, building the MOF composites with another phase can also be considered as a materials' design strategy for introducing some defects to MOF crystals.…”
mentioning
confidence: 99%
“…For the synthesis process leading to true composites and not to physical mixtures, the interactions of a MOF phase and modifier functional groups are important. Thus, owing to these interactions, the composites of Cu-BTC and oxidized g-C 3 N 4 had hierarchical porosity and exhibited photoactive properties [23].…”
mentioning
confidence: 99%
“…Over past years, composites of metal organic frameworks (MOFs) and inorganic nanomaterials have attracted much more attention for photocatalysis not only because of the significant charge separation by inducing charge carrier transfer at the interface of the composites, [1][2][3][4][5] but also due to the porous structure and high specific surface areas of MOFs, which lead to high loading capability and avoiding the agglomeration of inorganic nanomaterials. [6][7][8] To date, such inorganic nanomaterials mainly focus on SnO 2 , 9 PbO, 10 ZnO, 11 g-C 3 N 4 12 and TiO 2 . 13 For instance, Zhao et al used SnO 2 @UiO-66/rGO hybrid to degrade rhodamine B and achieved a 95.5% efficiency within 150 min.…”
Section: Introductionmentioning
confidence: 99%